The adeno-associated virus rep gene suppresses herpes simplex virus-induced DNA amplification. - Heilbronn, R (1990)
Herpes simplex virus (HSV) induces within the host cell genome DNA amplification which can be suppressed by coinfection with adeno-associated virus (AAV). To characterize the AAV functions mediating this effect, cloned AAV type 2 wild-type or mutant genomes were transfected into simian virus 40 (SV40)-transformed hamster cells together with the six HSV replication genes (encoding UL5, UL8, major DNA-binding protein, DNA polymerase, UL42, and UL52) which together are necessary and sufficient for the induction of SV40 DNA amplification (R. Heilbronn and H. zur Hausen, J. Virol. 63:3683-3692, 1989). The AAV rep gene was identified as being responsible for the complete inhibition of HSV-induced SV40 DNA amplification. Likewise, rep inhibited origin-dependent HSV replication. rep neither killed the transfected host cells nor interfered with gene expression from the cotransfected amplification genes. This points to a specific interference with HSV-induced DNA amplification.